2000
DOI: 10.1080/09670870050206073
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and status ofOecophylla smaragdina(Fabricius) as a pest control agent in citrus in the Mekong Delta, Vietnam

Abstract: Citrus farmers in the Mekong Delta have a long tradition of managing the weaver ant Oecophylla smaragdina (Fabricius). From 1994 to 1998, insecticide use increased significantly (P < 0.01) from 66% to 84% in orchards where O. smaragdina occurred. In 1998, ca 75% of the sweet orange (Citrus sinensis) and 25% of the Tieu mandarin (C. reticulata) orchards had large O. smaragdina populations, due to lower pesticide pressure in the first crop. In orchards with O. smaragdina, farmers sprayed less frequently and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 11 publications
2
53
0
1
Order By: Relevance
“…pollination (Van Mele & Cuc, 2000). According to Pickett and Carpenter (2010), this cosmopolitan subfamily has 958 described species in 26 genera, but the main diversity is in the Neotropical region, mainly in Brazil, with 21 genera and 304 recognized species (Carpenter, 2004).…”
mentioning
confidence: 99%
“…pollination (Van Mele & Cuc, 2000). According to Pickett and Carpenter (2010), this cosmopolitan subfamily has 958 described species in 26 genera, but the main diversity is in the Neotropical region, mainly in Brazil, with 21 genera and 304 recognized species (Carpenter, 2004).…”
mentioning
confidence: 99%
“…This study of ants feeding on eggs and immature borers of D. saccharalis revealed that, in plantations where the sugarcane straw is left on the ground in the crop, the immature stages of the borer prior to boring into the stems of sugarcane are at risk of being eaten by ants as: (1) baits of immature borers attract a greater number of ants; (2) ants are most abundant in the morning, both at baits consisting of eggs and immature individuals; (3) ant abundance varies from month to month and (4) Crematogaster sp.7, Pheidole sp.35 and S. saevissima are potentially important predators, given that they are commonly used to control pests (Way & Khoo, 1992;Van Mele & Cuc, 2000;Dejean et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ants are known predators of insect eggs (Rossi & Fowler, 2000;Van Mele & Cuc, 2000, 2001Way et al ., 1992Way et al ., , 1999. However, their action was not always beneficial.…”
Section: Discussionmentioning
confidence: 99%